Geographical Approach in the light of Modern Linguistics (Journal of the College of Basic Education, 2022)
There is no doubt that the linguistic research methods have become evident from the modern linguistic lesson. It necessitates that it becomes borrowed from the linguistic nature, and adapts the purpose that it sought for the purpose of study. Among the sciences that arose from general linguistics, geographical linguistics arose, synthesizing it in the sciences of sociology, psychology, anatomy and all its analogues, which leads to the modernity of linguistic sciences and the sobriety of actual applied study. Because of abundant patterns of pressures, from here geographical linguistics was the subject of the study of this research entitled ((Geographical Approach in the light of Modern Linguistics)).